(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The Gorontalo Outer Ring Road in Indonesia, a national route connecting three regions, is vital for enhancing economic development in the area. However, landslide problems are a significant concern in the Gorontalo region, threatening road safety and infrastructure stability. Landslide mitigation starts with slope stability analysis to provide recommendations for improving slope conditions and preventing landslides. This study aims to assess the Factor of Safety (FoS) values under the combined influence of rainfall and earthquakes at the study location. The methodology employed involves slope stability analysis that incorporates the effects of rainfall and earthquake-induced loads (Kh). Three conditions are analyzed: a condition without rainfall and earthquakes, a condition with rainfall effects and a condition with earthquake coefficients. Slope stability analysis is carried out using Seep/W and Slope/W from Geostudio 2021 software. The results indicate that under normal conditions (without rainfall and earthquakes), the FoS value is 1.150, while under the influence of rainfall the FoS value decreases to 0.818 and under the influence of earthquake coefficient, the FoS value becomes 0.746 indicating a significant risk of slope failure. These findings highlight that landslides in the study area are mainly triggered by the effects of rainfall and seismic activity, which significantly weaken the slope stability. On the other hand, the potential for landslides is considerably lower under dry conditions without seismic disturbances. The study underscores the importance of considering both rainfall and earthquake factors in landslide risk assessment and management.